An all metasurface-based fiber needle probe for Raman spectroscopy - Zhang, Shuyan; Bi, Renzhe; Zhang, Ruochong; Qi, Yi; Salim, Rasyiqah Bte Shaik Mohamed; Olivo, Malini (Frontiers in Physics, 2022)
Optical fiber-based spectroscopy sensors are widely used for industrial and biomedical applications. They normally consist of at least one excitation fiber and one collection fiber. However, the excitation and collection fibers are placed side by side, so the focal spots do not coincide. In addition, Raman probes whose excitation and emission span a wide wavelength range are limited by wavelength-dependent focal length variation, low sensitivity, and bulky size impeding their clinical adoption. To overcome the challenges, we propose an all metasurface integrated fiber solution. The metasurface technology is well suited for this application because it relies on specially designed nanostructures to manipulate light properties in an ultrathin footprint. Here we used our earlier demonstrated dual-wavelength excitation Raman probe as an example. The two excitation fibers at 671 nm and 785 nm feature a hybrid metasurface lens (metalens) including a narrow band pass filter and an off-axis focusing metalens. The collection fiber at 810 – 910 nm features an achromatic broadband on-axis focusing metalens. Simulation results show that by integrating the metalenses, the focal spots of the excitation beams and the collection beam coincide with a beam size of 4.6 µm, 4.6 µm, and 11.3 µm in the x-, y-, and z-axis, respectively. Moreover, the probe size shrinks by 100 times and becomes a needle probe. The needle probe will enable new applications such as small animal in vivo experiments, medical endoscopy experiments, and neonatal skin analysis for hard-to-reach areas. Furthermore, the proposed solution can be applied to work with any optical fiber-based spectroscopy sensors because the designs can be readily fabricated and put into practical use.